Hubungan Integritas Guru PAK Dalam Melaksanakan Tugas dan Tanggungjawab Terhadap Motivasi Belajar Siswa - Andrianus Nababan; Warseto Freddy Sihombing (Institut Agama Kristen Negeri Tarutung, 2021)
This study aims to determine the relationship and magnitude of Christian religious teacher’s integrity in carrying out their duties and responsibilities to students of SMP Negeri 2 Lintongnihuta. The number of samples here was 129 students. Data was collected by means of a questionnaire using descriptive analysis. The results showed that there was an effect of Christian religious teacher integrity in carrying out duties and responsibilities to students. This research was analyzed using descriptive and inferential statistical data analysis techniques with the following steps: (1) The relationship test found that rcount r table was 0.621 0.349. It can be concluded that there is a positive relationship between the Integrity of Christian religious Teachers with Duties and Responsibilities, (2) The significant test of the relationship shows that tcount t table is 4.338 2.042. Based on the results of this study, teachers of religious education must have integrity that greatly influences a person in carrying out their duties and responsibilities regularly, consistently, honestly, in accordance with the professional ethics code for Christian religious teachers. As result, student interest and motivation will increase.